Peningkatan Minat Belajar Siswa Melalui Pembelajaran E-Learning Via Whatsapp Di Kelas X MIPA Madrasah Aliyah Hasanah Pekanbaru - Dicky Ryan; Zulfah Zulfah (Journal on Education, 2021)
This research is based on the low interest in student learning towards teaching and learning activities through online. Because there is a limited knowledge of students who are not sensitive to technology and information, some students complain because of the difficulty in accessing this online learning. Even so, there are several learning applications that are free, but because of the low interest in students learning about learning applications and because of a lack of understanding of how to use them, here the researchers conducted student observations of online learning via WhatsApp. The purpose of this study was to determine how much influence the increase in online learning via WhatsApp on student interest in learning. This research is a collaborative classroom action research between the researcher, the teacher as the subject giving action and the students as the recipient of the action. This research was conducted at MA Hasannah in class X MIPA, with 13 students. The data collection method used by researchers is in the form of filling out a questionnaire using google form, while the research instrument is the questions that are presented on the questionnaire filling sheet on the google form. In this study it can be concluded that there is low student interest in online learning so that it affects student learning outcomes, so the solution is to use the WhatsApp application in online learning.